Are opioid antagonists effective in attenuating the core symptoms of autism spectrum conditions in children: a systematic review. (4th March 2014) - Roy, A.; Roy, M.; Deb, S.; Unwin, G.; Roy, A.
Abstract Background ASC (autism spectrum conditions) may result from a failure of striatal beta endorphins to diminish with maturation. Many symptoms of ASC resemble behaviours induced in animals or humans by opiate administration, including decreased socialisation, diminished crying, repetitive stereotypies, insensitivity to pain and motor hyperactivity. Naltrexone, an opioid antagonist, has been used in the management of children with ASC and can produce a clinically significant reduction in the serious and life‐threatening behaviour of self‐injury for individuals who have not been responsive to any other type of treatment and is important for this reason. It was therefore appropriate to reconsider the available evidence and a systematic review was undertaken. Methods Four electronic databases were searched for relevant journal articles. In addition, cross‐referencing of pertinent reviews and a hand search for articles in major international intellectual disability (ID) journals between the years 2010 and 2012 was carried out to ensure that all relevant articles were identified. We also searched databases for unpublished clinical trials to overcome publication bias. Each database was searched up to present (February 2013) with no restrictions on the date of publication. The search terms consisted of broad expressions used to describe ID and autistic spectrum disorder as well as terms relating to opioid antagonists and specific drugs. All studies identified by the electronic database search and hand search were examined on the basis of title alone for relevance and duplication. The abstracts of the remaining papers were then scrutinised against the inclusion criteria. Where abstracts failed to provide adequate information, the full texts for these papers were obtained. All the full texts were then evaluated against the inclusion proforma. Two reviewers carried out all the stages of the process independently. The reviewers met to discuss their selections and where disagreements arose, these were settled by discussion with a member of the study group. Data from each study meeting the inclusion criteria were extracted on a pre‐piloted data extraction form. The quality of each study was further assessed using the Jadad scale, a tool developed to assess the quality of randomised controlled trials. Results 155 children participated in 10 studies; 27 received placebo. Of the 128 that received naltrexone 98 (77%) showed statistically significant improvement in symptoms of irritability and hyperactivity. Side effects were mild and the drug was generally well tolerated. Conclusions Naltrexone may improve hyperactivity and restlessness in children with autism but there was not sufficient evidence that it had an impact on core features of autism in majority of the participants. It is likely that a subgroup of children with autism and abnormal endorphin levels may respond to naltrexone and identifying the characteristics of these children must become a priority.